2021
DOI: 10.1111/are.15309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stocking density on growth performance, plankton abundance, body composition and haematological parameters of Etroplus suratensis (Bloch, 1790)

Abstract: A seed rearing experiment was attempted to evaluate the effects of stocking densities in the biofilm-based system reared with pearlspot, Etroplus suratensis on different aquaculture parameters. Pearlspot advanced fry of size (4.67 ± 0.04 cm/1.71 ± 0.03 g) stocked at four different stocking densities viz 50 fish (T 1 ); 100 fish (T 2 ); 150 fish (T 3 ) and 200 fish (T 4 ) m −3 in the biofilm-based rearing system and at the rate of 150 fish m −3 in the clear water fed (CWF) system tanks. The total ammonia nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…association of photosynthetic microalgae and heterotrophic bacteria (Catarina and Xavier, 2012). It is also found that incorporation of algal bacterial system helps in improving the water quality by removal of harmful nitrogenous content from culture environment (Han et al, 2019;He et al, 2017;Pacheco-Vega et al, 2018;Yadav et al, 2021). The natural anti-microbial compounds or biomolecules in some microalgal species can serve as immunostimulants and improve the cultured organism's health (Charoonnart et al, 2018).…”
Section: O N L I N E C O P Ymentioning
confidence: 99%
See 3 more Smart Citations
“…association of photosynthetic microalgae and heterotrophic bacteria (Catarina and Xavier, 2012). It is also found that incorporation of algal bacterial system helps in improving the water quality by removal of harmful nitrogenous content from culture environment (Han et al, 2019;He et al, 2017;Pacheco-Vega et al, 2018;Yadav et al, 2021). The natural anti-microbial compounds or biomolecules in some microalgal species can serve as immunostimulants and improve the cultured organism's health (Charoonnart et al, 2018).…”
Section: O N L I N E C O P Ymentioning
confidence: 99%
“…Microbial films have been reported to improve the water quality parameters and alleviate harmful effects of the overloaded population (Krishnani et al, 2006a;Krishnani et al, 2009Krishnani et al, , 2013Krishnani and Kathiravan, 2010). Yadav et al (2021) reported a significantly lower value of total ammonia concentration in the biofilm rearing system than sources of clear water fed fish seed rearing system.…”
Section: Sr Yadav Et Al: Algal-bacterial Intervention For Aquaculturementioning
confidence: 99%
See 2 more Smart Citations